Biomass composition of azolla sp. growth in paddy field / Izzah Nadhirah Mohamed Zain - Mohamed Zain, Izzah Nadhirah (2014)
Azolla sp. was used by the farmers to improve the growth performance of paddy and also used as a substitute feeding materials for livestock. Three types of water sources (Kuala Pilah paddy field water, Tanjung Karang drain water and distilled water) each was used to study the growth performance of Azolla sp. and this experiment was conducted from February until March 2014. Growth performance of Azolla sp. in Tanjung Karang drain water show the highest result followed by Kuala Pilah paddy field water and distilled water as a control was the lowest. When Azolla sp. added with fertilizer (cow dung), the growth performance continue to increase until the end of experiment. The application of different amount of propagule which is 0.2 g of Azolla sp. showed the highest percentage of growth performance with 88%. Azolla sp. was applied in Kg. Ibol, Kuala Pilah paddy field and this experiment was conducted from March until May 2014.Growth performance of paddy plant in terms of height of paddy leaves and number of paddy leaves produces when applied with 5 g and 10 g of Azolla sp. higher compared with when no Azolla sp. added. Based on Tukey test conducted, the results indicates that there is significantly different between the control group which no Azolla sp. applied compared to application of 5 g and 10 g of this aquatic fern. Results obtained from this study shows that Azolla sp. can improve growth performance of paddy in terms of their height and number of paddy leaves produced. Further research about Azolla sp. can be done in order for this aquatic fern can be used to increase the paddy production.